Adnexal torsion in a heterotopic pregnancy: a rare clinical entity with diagnostic dilemma - Mohapatra, Kirtirekha; Mishra, Subhasri; Sahoo, Balaram; Marandi, Basudev; Sen, Rishika; N., Sagarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Adnexal torsion is an uncommon cause of surgical emergency during pregnancy. Its incidence is 1 in 5000 pregnancies, occurring more frequently in the first trimester after ovarian hyper stimulation. Heterotopic pregnancy is also a rare entity and cause pain abdomen but without the classical symptom of bleeding per vaginum. Heterotopic pregnancy with adnexal torsion is extremely rare but increases the case fatality rate. Hence the differential diagnosis of pain abdomen during early pregnancy both may be considered and it should not be forgotten that adnexal torsion may occur in absence of ovarian cyst. We report a case of adnexal torsion that was successfully managed by laparoscopy followed by laparotomy during pregnancy and diagnosed as a heterotopic pregnancy after getting the histopathological report. A 24-year-old G2P1 admitted to LR of SCBMCH at 4 weeks of GA with severe left abdominal pain and nausea for one day. Her vitals were stable. There was tenderness on the left iliac fossa with cervical motion tenderness and left POD fullness and tenderness, TAS visualized a foetus in utero with GA of 7 weeks and a hyperechoic mass of 6 x 6 cm on left side. Laparotomy done as the mass was gangrenous, enlarged and haemorhagic. Total salpingo oophorectomy of left side was done. Postoperative period was uneventful and managed with progesterone to continue the pregnancy. Histopathology report confirmed heterotopic pregnancy. This case suggests that clinicians should suspect both heterotopic pregnancy and adnexal torsion while evaluating pregnant patients with pain abdomen.